Selection and Verification of the Agitator in the Regeneration Tank - Lv Wei; WANG Shu-ying; LI Gui-hui; LI Jian (Journal of Harbin University of Science and Technology)
The regeneration efficiency of sodium ion is low because the regeneration reaction is not enough in the regeneration tankAccording to the data and requirements provided by the factory, combined with the experience of the design of the stirrer and the national standard, two agitators were designed for the regeneration tank, and the values of the two kinds of agitators were used We adopt simulation method to determine the speed distribution within the regeneration pool, turbulence distribution and then verify the success of the design of the mixer.